EPIDEMIOLOGICAL ASPECTS OF BLOOD EXPOSURE ACCIDENTS WITH THE HEALTHCARE WORKERS STAFF OF A PERIPHERAL HOSPITAL IN BENIN - Hinson, Antoine Vikkey; Lawin, Hervé; Gounongbe, Fabien; Aguêmon, Badirou; Sossa, Charles Jérome; Daddah, Donatien (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Aim: To assess the level of Blood Exposure Accidents (BEA) and suggest preventive measures to the health workers. Methods: It was one descriptive and cross-sectional study carried out in the hospital’s technical services from May to July 2014. Both the medical and paramedical staff had filled an anonymous questionnaire related to their socio-demographic profile, their history of BEA and their knowledge thereof. Results: Out of the 121 workers who took part in the study, 42(34.7%) were nurses, 40 (33.1%) auxiliary nurses, 14 (11.6%) laboratory technicians and 8 (6, 6%) were physicians. The sex ratio of the population is 1.28%.The worker’s immunization coverage against hepatitis B is 43.8%. 14.9% cases were reported BEA. The needle sticks injuries were the most frequent accidents (72.2%). Nurses, auxiliary nurses and laboratory technicians were the most affected respectively 33.3%, 27.8% and 16.7% cases. 61.1% of cases had their wounds disinfected immediately, but only 5.5% declared their injury. The main reason being the lack of knowledge of the declaration procedure (70.6%). Universal safety measures are not sufficiently known by the agents. Conclusion: Healthcare workers are exposed to a higher risk of BEA and most of the injuries are not declared. Sensitization must be carried on the respect of universal safety measures.